DJ‐1 regulates tyrosine hydroxylase expression through CaMKKβ/CaMKIV/CREB1 pathway in vitro and in vivo. Issue 2 (24th June 2019) - Xu, Xingyun; Wang, Rui; Hao, Zongbing; Wang, Guanghui; Mu, Chenchen; Ding, Jianqing; Sun, Wanping; Ren, Haigang
Abstract: Lack of dopamine production and neurodegeneration of dopaminergic neurons in the substantia nigra are considered as the major characteristics of Parkinson's disease, a prevalent movement disorder worldwide. DJ‐1 mutation leading to loss of its protein functions is a genetic factor of PD. In this study, our results illustrated that DJ‐1 can directly interact with Ca 2+ /calmodulin‐dependent protein kinase kinase β (CaMKKβ) and modifies the cAMP‐responsive element binding protein 1 (CREB1) activity, thus regulates tyrosine hydroxylase (TH) expression. In Dj‐1 knockout mouse substantia nigra, the levels of TH and the phosphorylation of CREB1 Ser133 are significantly decreased. Moreover, Dj‐1 deficiency suppresses the phosphorylation of CaMKIV (Thr196/200) and CREB1 (Ser133), subsequently inhibits TH expression in vitro. Furthermore, Knockdown of Creb1 abolishes the effects of DJ‐1 on TH regulation. Our data reveal a novel pathway in which DJ‐1 regulates CaMKKβ/CaMKIV/CREB1 activities to facilitate TH expression. Abstract : Loss of DJ‐1 decreases tyrosine hydroxylase (TH) expression in vitro and in vivo. DJ‐1 directly binds to Ca 2+ /calmodulin‐dependent protein kinase kinase β to regulate the activity of CaMKIV/cAMP‐responsive element binding protein 1 (CREB1) pathway. TH regulation by DJ‐1 is CREB1 dependent.